Research on the Current Situation and Countermeasures of Tourism Employment in Lishui City under the All-region Tourism - WANG, HAILI (Pacific International Journal, 2023)
With the release of optimized epidemic prevention and control policies in China, the tourism industry is experiencing a strong return. However, the post-epidemic tourism era has led to rapidly changing tourist demands, which have greatly increased the professional ability and quality requirements of tourism workers. Therefore, the post-epidemic tourism employment problem has become a concern for both the government and the industry. This paper analyzes the talent demand in the tourism industry in Lishui City under the background of all-regional tourism and makes suggestions. While the rapid development of tourism in Lishui City has brought about increased employment opportunities, the tourism labor market in Lishui still faces various challenges, such as a shortage of tourism management talents, low cultural quality of tourism workers, and lack of tourism professionals. In addition, employment quality has declined due to high worker mobility and personnel loss caused by COVID-19. To address these issues, this study proposes several measures: establishing the concept of all-round tourism, promoting high-quality development of tourism to create more jobs, improving the quality of tourism workers and services, adjusting the tourism employment system, and optimizing the employment structure of the tourism industry by adjusting its layout. This paper offers useful suggestions to address the challenges faced by the tourism industry in Lishui City in the post-epidemic era.